Between Science and Art: Thin Sound Absorbers Inspired by Slavic Ornaments - Krushynska, Anastasiia O. (Frontiers in Materials, 2019)
Acoustic metamaterials have opened fascinating opportunities for manipulation of low-frequency sound and development of compact structures with broadband acoustic performance for noise mitigation applications, room and architectural acoustics. So far, several mechanisms have been studied to achieve perfect sound absorption at subwavelength frequencies, when structural dimensions are much smaller than the wavelength of incident waves. Here, we analyze two alternative approaches based on the use of interacting and coupled resonators in absorbing panels with the aim to reduce the panel thickness. We numerically demonstrate that proper designs of interacting resonators allow extending a single-peak absorption to broadband frequencies, while the use of coupled resonators enables broadband absorption at several frequency ranges. The proposed configurations are inspired by ancient Slavic folk patterns with delicate ligature, multi-layered structure, and concealed meaning. Our results open new possibilities for creating acoustic metamaterials with added art effects, which individualize occupied space and make absorbing panels more appealing for various applications.